An overview of fasciolosis in human and cattle populations in New Valley, Egypt - Khedr, Abeer A.; Abdel-Hakeem, Sara Salah; Mahmoud, Wafaa G.; Abdel-Hakeem, Sally Salah; Al-Hakami, Ahmed M.; Tolba, Mohammed E. M.; Abd-Elrahman, Salwa Mahmoud; Khalifa, Mervat M. (Frontiers in Veterinary Science, 2025)
IntroductionFascioliasis, a significant global zoonotic disease caused by trematode parasites of the genus Fasciola, affects various livestock species.AimThis study aimed to identify demographic, epidemiological, clinical manifestations, pathological, and genetic characteristics in New Valley, Egypt's human, and cattle populations.MethodsThis study is made of two parts, the first part is a cohort study of 1000 cattle slaughtered at three abattoirs in El Kharja, El Dakhilah, and El Farafra from February 2023 to January 2024. A retrospective analysis of patients visiting El Kharja hospital with clinical symptoms and confirmed with coprological and radiological examinations.ResultsThe study revealed a high prevalence in cattle (23%) and humans (3.6%). Enrolled human fascioliasis was diagnosed in 58.3% and 41.7% by coprological and radiological analysis, respectively. A 66.7% of enrolled cases were females, with a median age range of 37 ± 13 years old. Treatment outcomes demonstrated a response of 25%, 50%, and 25% to single, two, and three doses of the treatment, respectively. In cattle, infection rate was 20.0% in females compared to 24.9% in males with low prevalence in animals <1 year (12.7%) and high in animals >3 years (30.4%). Autumn had the highest prevalence (28.7%), whereas summer had the lowest prevalence (18.0%). A significant difference in the prevalence of fasciolasis was observed between human and animals. Morphological and histopathological analysis elucidated acute and chronic manifestations of hepatic fascioliasis with ectopic migration to cattle lung tissue. Genetic characterization of ectopic worm confirmed Fasciola hepatica infection, with genetic similarity to human isolates from Iran.DiscussionThe study highlights the importance of one health approach in understanding and managing fascioliasis.